CODE SWITCHING AND CODE MIXING IN EFL CLASS AT HOMESCHOOLING KHALIFAH - Hanifah Nabighah Kultsum; Oom Rohmah Syamsudin (Universitas Indraprasta PGRI, 2021)
Abstract: This study aims to determine: (1) The type of code-switching and code-mixing used, (2) The function of code-switching and code-mixing used by teachers and students, (3) The reason teachers and students use code-switching and code-mixing. This research was conducted using a qualitative descriptive method. Data collection in this study was carried out by observation, questionnaire, and interview and then analyzed and describing the results. The results show: (1) The types of code-switching and code-mixing often used are the type of intrasentential code-switching is 50.7%. Furthermore, the type of code-mixing alternation is 46.2%. (2) The code-switching and code-mixing functions used by teachers and students are as easy communication as is 42.5%. (3) Teachers and students use code-switching and code-mixing to facilitate communication in class and understand the material presented by the teacher.Keywords: Code Switching, Code Mixing, EFL Class.